Investigating the origin of solutes in rock glacier springs in the Swiss Alps: A conceptual model - Del Siro, Chantal; Scapozza, Cristian; Perga, Marie-Elodie; Lambiel, Christophe (Frontiers in Earth Science, 2023)
In the current context of climate change, rock glaciers represent potentially important water resources due to the melting of ice they contain and/or their role as high mountain water reservoirs. However, the hydrology of these high-altitude debris accumulations is poorly known. Understanding the origin and quality of rock glacier outflows is essential to evaluate their contribution and impact on headwater systems. In this study, we developed a conceptual model explaining the main hydro-chemical processes in active rock glaciers in the current context of permafrost warming. This conceptual model was derived from isotopic and physico-chemical analyses performed on six rock glacier outflows in the Swiss Alps during the warm season. Similar chemical and isotopic analyses were performed in sources not fed by rock glaciers at all study sites. The ion content (SO42-, Ca2+, Mg2+ and NO3-) of the water emerging from active rock glaciers was globally higher than that of sources not fed by rock glaciers. Besides, the electrical conductivity and the ion content (SO42-, Ca2+ and Mg2+) of the active rock glacier springs increased during the warm season, tracking the increasing perennial ground ice melting. We hypothesized that the ionic fingerprint of melting ice points mainly to the remobilization of chemical compounds stored during a colder period of the past in the cryosphere (e.g. the 1960s-1980s).